The genus Microdonophagus Schauff (Hymenoptera: Eulophidae), with description of a new species - Hansson, Christer (Zootaxa, 2009)
A second species of the hitherto monotypic genus Microdonophagus Schauff is described as Microdonophagus levis sp. nov. The species is described from material collected at La Selva Biological Research Station in Costa Rica. Unlike the previously described species, Microdonophagus woodleyi Schauff, it is described from females only and the biology is not known. The addition of a second species of Microdonophagus enhances the possibilities to assess the characters defining the genus, some of which are introduced as new here.